Understanding the media - Devereux, Eoin (London SAGE Publications Ltd, 2014)
How much of our media experience is shaped by the profit motive of media conglomerates? How much do we have freedom and power as members of an increasingly fragmented media audience? How do music, television and social media influence what we understand about friendship, fun, political events, democracy, globalization and even our own selves? This book teaches students how to ask critical questions of the media, and gives them the analytical tools to answer those questions. Students will gain a rich understanding of how the media play a role in society, both in giving pleasures and creating power relationships.
Understanding the media -- Media histories, media power -- Media globalization -- Media ownership : concentration, conglomeration and regulation -- Media professionals and media production -- Media ideologies and discourse -- Media 're-presentations' in an unequal world -- Media audiences and reception -- New media, social media -- Conclusion : The how and why media analysis.
Includes bibliographical references (pages 301-322) and index.
Keywords: Mass media; Media Studies